2010
DOI: 10.1007/s00787-010-0109-5
|View full text |Cite
|
Sign up to set email alerts
|

Neurofeedback training in children with ADHD: 6-month follow-up of a randomised controlled trial

Abstract: Neurofeedback (NF) could help to improve attentional and self-management capabilities in children with attention-deficit/hyperactivity disorder (ADHD). In a randomised controlled trial, NF training was found to be superior to a computerised attention skills training (AST) (Gevensleben et al. in J Child Psychol Psychiatry 50(7):780–789, 2009). In the present paper, treatment effects at 6-month follow-up were studied. 94 children with ADHD, aged 8–12 years, completed either 36 sessions of NF training (n = 59) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
139
2
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(153 citation statements)
references
References 25 publications
6
139
2
6
Order By: Relevance
“…Two years after the end of the study, the behavioral and attentional improvements were maintained and some additional benefits could be seen, suggesting that patients were still improving even after the end of treatment. Gevensleben et al [60] found similar results in the 6-month follow-up of their randomized controlled trial comparing NF to CAST. Sixtyfive percent of participants were followed, and improvements in the NF group were superior to the control group and comparable to that of the end of the active treatment phase.…”
Section: Is Long-term Nf Effective?mentioning
confidence: 67%
See 1 more Smart Citation
“…Two years after the end of the study, the behavioral and attentional improvements were maintained and some additional benefits could be seen, suggesting that patients were still improving even after the end of treatment. Gevensleben et al [60] found similar results in the 6-month follow-up of their randomized controlled trial comparing NF to CAST. Sixtyfive percent of participants were followed, and improvements in the NF group were superior to the control group and comparable to that of the end of the active treatment phase.…”
Section: Is Long-term Nf Effective?mentioning
confidence: 67%
“…Gevensleben et al [60] defined response ratio as a reduction of at least 25 % in symptoms, and found 50 % of participants to respond to NF, suggesting that some individuals may benefit from NF, whereas others may not. Wangler et al [61] found baseline EEG patterns, specifically, an increase of the CNV in an attention task, to be a predictor of good response to SCP training.…”
Section: Which Adhd Subtypes Benefit From Nf?mentioning
confidence: 99%
“…A major advantage of neurofeedback and other neurotherapeutic approaches 63 over typical pharmacologic interventions (as for other behavioral, learning-based interventions) is the potential for sustained, long-term benefits after successful completion of treatment. Investigations 36 indeed found positive effects on ADHD symptoms being stable 6 months after training.…”
Section: Stability Over Timementioning
confidence: 99%
“…Meta‐analyses of randomized controlled trials (RCT) of EEG‐NF show medium effect sizes for symptom improvements [Arns et al, 2009], reduced to trends when only “probably” blinded raters are included [Holtmann et al, 2014; Sonuga‐Barke et al, 2013]. Crucially, unlike psychostimulant treatment, NF effects seem stable and longer‐lasting (up to 2 years), with no side effects [Arns and Kenemans, 2014; Gani et al, 2008; Gevensleben et al, 2010; Leins et al, 2007; Mayer et al, 2016; Steiner et al, 2014; Strehl et al, 2006]. …”
Section: Introductionmentioning
confidence: 99%